ANALYSIS EFFECT OF THE PRIMARY PULLEY ANGLE OF SPORTY MOTORBIKE - Nurlaila, Qomarotun; Ryadin, Agus Umar; Yanto S, Dedi (Fakultas Teknik, Universitas Riau Kepulauan, 2024)
The research aims to analyze the effect of the primary pulley slope angle on engine torque and fuel consumption of the Mio Sporty 115 CC motorbike. The inclination angle of the primary pulley based on factory standards is 14º. Changing the slope angle of the primary pulley using a lathe for angles of 12º, 13º and 13.5º. Testing was carried out using a dyno test machine, 3 data for each slope angle. The dyno test results consist of engine speed, torque, and power. Fuel consumption is obtained using calculations based on test data. Based on the analysis of test results and calculations, it is known that the slope angle of the primary pulley affects engine torque and fuel consumption of the Mio Sporty 115 CC motorbike. The 14º slope angle produces 6.35 torque, the 13.5º slope angle produces 6.47, the 13º slope angle produces 6.29 and the 12º slope angle produces 6.02. Meanwhile, for fuel consumption, slope angle 12º and 14º require fuel consumption of 0.19 l/hour, slope angle 13º & 13.5º require fuel consumption of 0.18 l/hour. Based on the highest torque and the lowest fuel consumption results, a slope angle of 13.5º is recommended.